Evaluasi Strategi Penanganan Permukiman Kumuh Dalam Mendukung Peningkatan Kualitas Lingkungan Hidup Di Kelurahan Karang Anyar Pantai Kota Tarakan - Marzuki, Marzuki; Setianto, Yohannes Agus; Sodikin, Sodikin (Universitas Tanjungpura, 2023)
The city of Tarakan is one of the target cities for migrants (urbanists) to live in. The economic limitations of migrant communities and local communities to have decent housing will then trigger the growth of new slum settlements. The aim of the study is to evaluate slum management strategies, identify environmental conditions and reformulate slum management program strategies. The research method uses a qualitative descriptive approach. Research tool with Questionnaire and Laboratory Analysis. The research locus was in 12 RT in the Karang Anyar sub-district, Tarakan City. Communal WWTP wastewater samples, solid waste data, river water and clean water. Data analysis used the Pollution Index, Sanitation Risk Index, Quality Standards and Analytical Hierarchy Process (AHP) methods. The results of the research on the evaluation of slum management strategies with a score of 18 so that they are still in mild slum conditions. There are four aspects of the performance achievement level with the realization of a very high performance achievement rate of above 90%, one aspect of a high performance achievement level of above 76%, and the environmental road aspect with an achievement level of 54.01% is a low level of realization. Results Identification of environmental conditions at inlets, outlets, bodies of water with parameters COD, TSS, Ammonia, Oil and Grease did not meet quality standards and analysis of Pollution Index (Pi) in Light Polluted conditions. The quality of waste management is based on the Sanitation Risk Index (IRS) score for 12 RTs with an average high-risk area. Clean Water Quality with parameters (Total Coliform and E. Coli) results meet drinking water quality standards. From the results of the AHP analysis, the Infrastructure and Facilities Development Strategy is a top priority. Consistency value of 0.05 or 0.1 comparison matrix is consistent.